Semantic and Aspectual Opposition of Verbs: Cause and Effect - Милослaвский И. Г. (Kalbotyra, 1988)
The article deals with a still unsolved problem in linguistics concerning the correlation of semantic and aspectual properties of the verbs. A broad analogy with other grammatical categories is drawn, and it is claimed that theoretical and lexicographical description of the Russian verb system should be based on the semantic but not on the grammatical characteristics of the verb.